Cost-effectiveness of a comprehensive programme for drug-resistant tuberculosis in China - Christopher Fitzpatrick; Zhang Hui; Wang Lixia; Li Renzhong; Ruan Yunzhou; Chen Mingting; Zhao Yanlin; Zhao Jin; Su Wei; Xu Caihong; Chen Cheng; Timothy Alston; et al.
Abstract Objective To investigate the cost-effectiveness of a comprehensive programme for drug-resistant tuberculosis launched in four sites in China in 2011. Methods In 2011-2012, we reviewed the records of 172 patients with drug-resistant tuberculosis who enrolled in the comprehensive programme and we collected relevant administrative data from hospitals and China's public health agency. For comparison, we examined a cohort of 81 patients who were treated for drug-resistant tuberculosis in 2006−2009. We performed a cost-effectiveness analysis, from a societal perspective, that included probabilistic uncertainty. We measured early treatment outcomes based on three-month culture results and modelled longer-term outcomes to facilitate estimation of the comprehensive programme's cost per disability-adjusted life-year (DALY) averted. Findings The comprehensive programme cost 8837 United States dollars (US$) per patient treated. Low enrolment rates meant that some fixed costs were higher, per patient, than expected. Although the comprehensive programme appeared 30 times more costly than the previous one, it resulted in greater health benefits. The comprehensive programme, which cost US$ 639 (95% credible interval: 112 to 1322) per DALY averted, satisfied the World Health Organization's criterion for a very cost-effective intervention. Conclusion The comprehensive programme, which included rapid screening, standardized care and financial protection, improved individual outcomes for MDR tuberculosis in a cost-effective manner. To support post-2015 global heath targets, the comprehensive programme should be expanded to non-residents and other areas of China.